Konstruksi Makna Al-Watan dalam Puisi Mahmoud Darwish: Analisis Semiotik Michael Riffaterre Terhadap Simbol Al-Nakhlah - Hanun Khiyarotun Nisa' (Journal of Transdisciplinary Studies in Religion and Education, 2026)
This study aims to reveal the construction of meaning of al-watan (homeland) in Mahmoud Darwish's poetry through Michael Riffaterre's semiotic approach. The research focuses on reading the symbol al-nakhlah (date palm) as the center of semiosis, representing land, identity, collective memory, and forms of cultural resistance against colonialism. Using qualitative descriptive methods based on literary semiotics, this study analyzes Darwish's poetry through two stages of reading, heuristic and hermeneutic, as well as identifying potential and actual hipograms to determine the matrix and model of the poem. The research results show that the symbol al-nakhlah functions not only as a metaphor for al-watan but also represents genealogical roots, the continuity of collective identity, and an existential body that cannot be separated from human existence. The poem constructs the meaning of homeland not merely as geographic space but as body, memory, affective experience, and a form of resistance against attempts to erase identity. The novelty of this research lies in reading al-watan as ontological identity through the framework of Riffaterre's semiotics, a framework that has not been widely applied to contemporary Arab literature in the postcolonial context.